Microtubules and mitochondria nanotunnels - Lavorato, Manuela (2018)
Mitochondrial function strictly depends on mitochondrial structure, location and dynamics. Mitochondria and cytoskeleton interaction is crucial for normal mitochondrial morphology distribution and motility. In cardiac muscle, microtubules sustain muscle contraction and mitochondria disposition; the latter is crucial for localized uptake of calcium (Ca2+) and consequentially energy production needed for cardiac function. Few studies have been conducted on understanding mitochondria and microtubules interaction in cardiomyocytes. In cardiac muscle, recent studies have shown that cardiac mitochondria do not need to migrate to communicate with each other, but they can extend protrusions called nanotunnels to reach and communicate with other mitochondria in long-distance. This process does not involve mitochondria movement, but possibly involves a pulling action along microtubules. The association of mitochondria nanotunnels and microtubules have been identified using 2D and 3D electron microscopy [1]. These new findings highlight the need to investigate the action of microtubules on cardiac mitochondria and its effect on mitochondria dynamics and cardiac function.